Epidemiology of traumatic spinal cord injuries in Colombia - Giraldo, Yalisma Andrea. (Spinal Cord Ser Cases, 2021)
STUDY DESIGN: Retrospective cohort study. OBJECTIVES: To determine the incidence and characteristics of newly injured individuals admitted to a traumatic spinal cord injury (TSCI) referral center during a 4-year period. SETTING: University Hospital of Valle, Cali, Colombia. METHODS: Individuals were identified, and their data was recorded based on the International Spinal Cord Injury Core Data Set. The outcome of interest was the American Spinal Injury Association Impairment Scale (AIS) grade at the last follow-up. RESULTS: There were 491 individuals admitted in the 4-year period. The mean annual incidence of TSCI was 56.27 per million inhabitants. Considering TSCI in individuals exclusively from Cali, the mean annual incidence was 27.78 per million. The leading cause of TSCI was interpersonal violence (47.25%) and falls (33.60%). There was a strong correlation between AIS grade at admission and last follow-up. The most common AIS grade at the last follow-up was E (34.01%) caused mostly by falls (57.48%), followed by A (31.16%) caused mostly by interpersonal violence (76.27%). The reported employment rate dropped from 75.56% to 18.94% before and after TSCI (p < 0.05). AIS grade A was associated with more post-injury complications (p < 0.05). CONCLUSIONS: This is the first cohort study in Colombia describing the incidence and AIS grades of individuals with TSCI from a trauma referral center. Interpersonal violence was overrepresented in this population. Future research should include the evaluation of prevention strategies, as well as research on interventions towards quality improvement in patient care and post-discharge services especially for individuals with AIS grade A.